Szkoła polska z lat ofensywy ideologicznej w oświacie (1948–1956) w świetle antologii wspomnień nauczycieli - Rozmarynowski, Marcin (Biuletyn Historii Wychowania, 2020)
The aim of the article is to present the assumptions and methods behind the ideological pressure exerted on Polish teachers by the communist authorities in 1948–1956 as described in the teachers’ memoirs. The Polish Workers’ Party (later the Polish United Workers’ Party) during the Stalinist period tried to instil in teachers “socialist morality” by means of courses, conferences, additional education and an order to “self-educate”. The text contains a synthetic historical outline of the above-mentioned activities and their analysis based on the memories of credible witnesses to those events.